PEMANTAUAN DAN PENGENDALIAN SUHU DAN KELEMBAPAN UDARA UNTUK TANAMAN TOMAT DENGAN MENGGUNAKAN WEMOS D1 - Wijaya, Toby; Ghozali, Theresia; Bachri, Karel Octavianus (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2025)
Plant cultivation process is an important component in creating optimal harvest results. Those results can be affected by both air temperature and humidity in the plant’s environment. Traditional method for monitoring and controlling temperature and humidity consume a lot of time and energy. This Wemos D1 and ThingSpeak equipped monitoring and controlling system was made in order to make those works easier. The system uses air temperature and humidity sensor which will perform reading to the environment’s condition. Datas collected from the reading progress will be forwarded by Wemos D1 to ThingSpeak so it can be observed by users. Exhaust fan and mist maker will be used as controlling components for the environment. This system is expected to help in developing plant cultivation techniques.